Ondansetrón vs dexametasona en el tratamiento de náusea y vómito postoperatorio. revisión sistemática - Rea Negrete, Paola Estefanía (2025)
Heartburn and vomiting represent the most common postoperative complications caused by a combination of factors of both surgical and physiological nature of each individual. These complications can lead to serious health problems such as: dehydration, electrolyte imbalance, aspiration of gastric contents that can provoke pneumonia, esophageal rupture and hemorrhage, resulting in prolonged hospitalization, delayed discharge from hospital, prolonged recovery and increased costs to the health care system. Therefore, the aim of this study was to compare the effectiveness of ondansetron and dexamethasone in the treatment of postoperative heartburn and vomiting by means of a systematic review of the scientific literature, which was carried out through a qualitative approach a non - experimental design and an exploratory study. On the other hand, in the theoretical method, the analytical - synthetic method was used, allowing the study of the behavior of each party through critical reading and analysis of the perspectives of each individual, resulting in the identification of the shortcomings in the management of ondansetron vs dexamethasone in the treatment of postoperative nausea and vomiting, consolidating the scientific information in relation to the aforementioned drugs, promoting individualized health care, based on critical and analytical thinking that enhances nursing care and prognosis of the